Partisipasi Masyarakat Urban dalam Pengelolaan Sampah di Bank Sampah Induk Kota Magelang Untuk Mendukung Pembangunan Berkelanjutan - Joko, Joko Tri Nugraha; Aflah, Aflah Amrulloh; Ari, Ari Mukti; Eny, Eny Boedi Orbawati (Economics and Digital Business Review, 2025)
Community participation in waste management is a key factor in maintaining urban cleanliness. Magelang City faces an increasing volume of waste every year, the majority of which originates from residential areas. The Magelang City Government has established a Central Waste Bank as a community-based solution for waste management. This study aims to analyze community participation in the waste bank program as well as the driving factors that encourage its sustainability. The research method used is qualitative with a case study approach. Data collection techniques include interviews, observations, and document analysis. The results show that the level of community participation in managing waste remains low. Driving factors such as time, benefits, program relevance, individual capability, communication, sense of security, and flexibility encourage participation. Additionally, opportunity, willingness, and ability are also major motivators. It was found that those already involved experience social, environmental, and economic benefits despite economic incentives still being perceived as insignificant. This study recommends strategies to increase participation through education, continuous training, interactive communication, and multi-stakeholder synergy to make waste management more effective and sustainable.